2013
DOI: 10.1177/0734242x13476746
|View full text |Cite
|
Sign up to set email alerts
|

Recycling behaviour of householders living in multicultural urban area: a case study of Järva, Stockholm, Sweden

Abstract: The recycling behaviour of multicultural householders was investigated in the urban area of Järva, northwest Stockholm, Sweden, which is home to a significant proportion of immigrants from different parts of the world. Different ethnic minorities currently make up an important proportion of the urban population in Sweden, but little is known about their recycling behaviour and attitudes. Using quantitative (questionnaire) and qualitative (interviews) methodology, possible determinants of recycling behaviour we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
53
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 25 publications
9
53
2
1
Order By: Relevance
“…Moral obligation was found to be the weakest determinant of health workers' HCW segregation behaviors which is in contrast to the results of previous studies [16, 31] where moral obligation was found to be the strongest determinant of behavior. Ajzen [10] recommended the addition of moral obligation to some contexts so as to improve the predictive strength of the TPB.…”
Section: Discussioncontrasting
confidence: 99%
“…Moral obligation was found to be the weakest determinant of health workers' HCW segregation behaviors which is in contrast to the results of previous studies [16, 31] where moral obligation was found to be the strongest determinant of behavior. Ajzen [10] recommended the addition of moral obligation to some contexts so as to improve the predictive strength of the TPB.…”
Section: Discussioncontrasting
confidence: 99%
“…The studies included are of qualitative, quantitative and mixed method design and descriptive information on them can be found in Appendix A. The publications by Miafodzyeva et al [24], Gregson et al [25], and Bonatti [26] study waste sorting among people with an immigration background or ethnic minorities. All other resource recovery studies that were included in this review do not study waste sorting among people with an immigration background per se, but meet the inclusion criteria because information on waste sorting among ethnic groups or immigrants was presented as a byproduct of their objectives [27][28][29][30][31][32][33].…”
Section: Resultsmentioning
confidence: 99%
“…Waste sorting and recycling among people with an immigration background and ethnic minorities were mentioned in studies that were conducted in Italy [26]; Northern Europe and the UK [25]; the UK [30][31][32][33]; the Netherlands [28]; and Sweden [24,27,29]. All these studies used the concept of 'recycling' rather than 'waste sorting'.…”
Section: Resultsmentioning
confidence: 99%
“…The review also focuses on the sorting of the food packaging waste carried out by the households. Sorting of food packaging waste is done in an attempt to manage this waste fraction at the proper level in the waste hierarchy, i.e., recycling [5,43]. Similar to previous studies, the act of sorting the waste for preparing the packaging for material recycling is also called 'recycling behavior'.…”
Section: Materials Collectionmentioning
confidence: 95%